REPRESENTASI PERAN GENDER PADA IKLAN VIDEO TUKAR TEMPAT DI KANAL YOUTUBE CERDAS BERKARAKTER KEMENDIKBUD RI - Elizabeth Rose Marie Yudistanti; Catur Suratnoaji (Linimasa : Jurnal Ilmu Komunikasi, 2023)
Advertising is a form of mass media product that presents various benefits. In modern times, advertising has developed so that it is made in new media in the form of social media. This study discusses the Indonesian Ministry of Education and Culture's "Tukar Tempat" advertisement, which is an audio-visual advertisement has been published on the Cerdas Berkarakter Kemendikbud RI Youtube channel. Tukar Tempat is a public service advertisement with the theme of gender with the issues discussed in this study the gender role of the husband figure who also has a background in the Covid-19 pandemic phenomenon which has an impact on the realm of domestic life. The purpose of this study is to determine the representation of gender roles in Tukar Tempat as public service advertisements with John Fiske's semiotic analysis in 12 scenes. This research is a descriptive qualitative research using John Fiske's semiotic analysis which consists of the level of reality, the level of representation, and the level of ideology. The data collection technique uses primary sources in the form of scene snippets of the "Tukar Tempat" video advertisement on YouTube and secondary sources from books, journals and relevant articles. The results of the study show that the depiction of gender roles in the reality level shows characteristics of masculinity, the level of representation of gender roles in the domestic sphere is weak, and the level of advertising represents gender roles followed by ideologies, gender, feminism, masculinity, patriarchy and matriarchy, domesticity, male chauvinism.